Literature Review Dosis Radiasi Pada Pemeriksaan Radiografi Thorax Anak - Akhmadi Akhmadi (Universitas Muhamadiyah Manado, 2022)
Thorax radiology examination in children is one of the most frequently performed examinations in hospitals. However, the radiation used in this examination can potentially disrupt the growth and function of the child's imperfect organs. Therefore, patient radiation protection is very important to optimize the radiation dose received. The Nuclear Energy Regulatory Agency (BAPETEN) has set reference level values ​​in the form of IDRL (Indonesia Reference Level) for Diagnostic Radiology, including CT-Scan, Mammography and Fluorescence, as well as DRL (Diagnostic Reference Level) values ​​for children's thorax. The radiation dose received by the patient must be considered to avoid negative effects on the child's growth. This study aims to determine the measurement of radiation dose on chest radiography examinations of children. In this study, we will compare the radiation dose received by pediatric thorax patients based on the radiation dose standards set by UNSCEAR in 2000. Apart from that, we will also compare the radiation dose received by pediatric thorax patients with other studies. It is hoped that the results of this research will provide useful information and input for hospital diagnostic services in optimizing the radiation dose received by pediatric patients.